Glass ionomer cement modified by a imidazolium salt: adding antifungal properties to a biomaterial - Ehrhardt, Alexandre; Mandelli, Jéssica Zolim Andreatto; Bérgamo, Vanessa; Lopes, William; Donato, Ricardo Keitel; Zanette, Régis A; Fuentefria, Alexandre Meneghello (Brazilian journal of microbiology, 2021)
We present the structural modification of a commercially available glass ionomer cement by inserting the imidazolium salt 1-n-hexadecyl-3-methylimidazolium chloride (C16MImCl), composing a new biomaterial with antifungal biofilm activity. Test specimens were prepared using a commercial glass ionomer cement to which 10 ppm of cetylpyridinium chloride (reference ionic antifungal agent) or C16MImCl were added. The feasibility and hypoallergenicity of the new biomaterial were assessed by microhardness plastic deformation and chorioallantoic membrane assays. Colony counting and scanning electron microscopy were used to evaluate the modified specimens' antibiofilm activity against three multidrug-resistant Candida species. The modified glass ionomer cement presented a strong antibiofilm activity against Candida spp., without losing its original micromechanical and hypoallergenic properties, rendering it a promising candidate for further application in dentistry.
Keywords: mikroskopie elektronová rastrovací; Microscopy, Electron, Scanning; Surface Properties; skloionomerní cementy; biokompatibilní materiály; imidazoly; Candida; antifungální látky; Biocompatible Materials; Biofilms; povrchové vlastnosti; Antifungal Agents; biofilmy; Glass Ionomer Cements; Imidazoles